Contamination of Local Laying Hen’s Egg Shell with Salmonella Serotypes: Maysoon R. Jaffer@ and Khulood K. Nazal - Jaffer, Maysoon R. (The Iraqi Journal of Veterinary Medicine, 2013)
Fifty locally laying hen’s eggs random samples were collected from different markets of Baghdad city in order to investigate the presence of Salmonellae Spp. in shell of those eggs. The samples were collected during the period from March 2012 to May 2012.The samples were directly transferred to the Food hygiene laboratory and analyzed immediately without further storage.The isolation and identification methods include: (pre-enrichment) culture stage by peptone water then, (Selective enrichment) culture stage by selenite broth after that culturing on sold (Selective media) which was Bismuth Sulphate agar. The biotyping by using API strip according to the API 20E miniaturized identification system for Salmonella SPP.. The isolated Salmonella strains were transferred on TSI agar to undergone sereotyping at the Institute of Public Health,Baghdad,Iraq. Data revealed that 15 out of the total 50 (30%) of the eggs samples were contaminated with Salmonella spp. Salmonella typhimurium and Salmonella enteritidis were the two serotypes that have been found in this study. Nine from 15 (60%) of the isolates was belong to Salmonella enteritidis serotypes while 6 from 15 (40%) of the isolates was belong to Salmonella typhimuriumserotype.